ETIOLOGY, DIAGNOSIS, AND MANAGEMENT OF CHILDHOOD MICROCEPHALY: A SINGLE-CENTER RETROSPECTIVE STUDY - Deniz Güven; Didem Ardıçlı; Dilek Sarıcı (MNJ (Malang Neurology Journal), 2022)
Background: Microcephaly is a condition that causes a reduction in brain volume as well as cognitive and motor impairments. It can be seen alone or in conjunction with a variety of genetic disorders and environmental factors. Microcephaly is still a poorly defined condition, identifying the etiological causes is critical for providing genetic counseling, and preventing potential consequences. Objective: The aim of this study was to assess the etiology, diagnosis, and management of the childhood microcephaly. Methods: We conducted a retrospective analysis on 50 children with microcephaly (25 males, 25 females) who presented to University of Health Sciences, Ankara Keçiören Training and Research Hospital between 2017-2021.The demographic features of the patients, neuroimaging, clinical and laboratory findings were examined. Results: The etiology of microcephaly was documented in 76% of all patients. Genetic causes were identified in 16 % of the patients; including Aicardi Goutieres Syndrome,Williams Syndrome , Wolfram Syndrome, Rett Syndrome and Asparagine Synthetase Deficiency. Syndactyly, scoliosis, Poland syndrome, dysmorphic face, alopecia, auricular ear deformities, hearing loss, strabismus, nystagmus, hydronephrosis, single umbilical artery, and cardiac septal defect were detected systemic malformations associated with microcephaly. In sixty percent of the patients, a neuroimaging was performed; results were abnormal in 24% of the patients. The mean follow-up period of the patients was 1.88± 0.6 years. Cognitive impairment was associated with microcephaly in 38% of the cases, and epilepsy in 20%. Of those 28% of the children required special education. One patient was operated by neurosurgeon due to craniosynostosis. Conclusion: Microcephaly is still a poorly defined condition, identifying the etiological causes is critical for providing genetic counseling, and preventing potential consequences.